1985
DOI: 10.1159/000249525
|View full text |Cite
|
Sign up to set email alerts
|

Sebum Suppression by Benzoylperoxide

Abstract: Sebum excretion rate (SER) was determined by thin-layer chromatography and based on densitometric data in 9 male and 5 female patients suffering from acne during treatment with 10% benzoylperoxide (BPO). BPO was applied to the forehead (treatment area), whereas gel only was applied to the chest (control area) for 6 weeks. SER decreased in 10/14 subjects, no change was found in 1 subject and 3 patients exhibited an increase in SER. Suppression varied between 12 and 86%. Concomitant SER reduction in control and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…With regard to previous data, it is known that CDP does not alter sebum production 2,3 . Although there are conflicting data, it has been generally shown that BPO does not suppress sebum production 8,21,22 . In one study, CDP + BPO application was associated with mild dryness and decreased SC hydration 23 .…”
Section: Discussionmentioning
confidence: 97%
“…With regard to previous data, it is known that CDP does not alter sebum production 2,3 . Although there are conflicting data, it has been generally shown that BPO does not suppress sebum production 8,21,22 . In one study, CDP + BPO application was associated with mild dryness and decreased SC hydration 23 .…”
Section: Discussionmentioning
confidence: 97%
“…Other authors report that benzoyl peroxide has neither a positive nor a negative influence on sebaceous secretion whatsoever after topical treatment, attributing the discrepancy in results to the different measuring methods used on the cutaneous lipids and the different conditions when measuring 19 . Lastly, some authors found suppressive action on the sebaceous production 20 …”
Section: Discussionmentioning
confidence: 97%
“…19 Lastly, some authors found suppressive action on the sebaceous production. 20 As far as adapalene is concerned, most of the scientific works do not highlight any significant effect on the secretion of sebum, even if some authors support the fact that it reduces sebaceous secretion, although with a limited effect over time. 10,21,22 Our study confirms that the three topical ingredients act in different ways on the sebaceous secretion.…”
Section: Discussionmentioning
confidence: 99%
“…These elements might explain the elevation of sebum excretion that would reduce the colonization of bacteria in the pilosebaceous unit, therefore preventing the onset of inflamed lesions [46]. Contrasting with Cunliffe's results, Schmidt et al [47] suggested that benzoyl peroxide may affect the sebum excretion rate in some patients only whereas Burkhart et al [48] asserted that benzoyl peroxide does not have sebosuppressive capabilities. So far, isotretinoin and hormonal therapies are the only drugs that can reduce sebum production (see further).…”
Section: Seborrhea and Acne: Inseparable Players Of The Pathogenic Prmentioning
confidence: 99%